Age-Dependent Accumulation of 8-Oxoguanine in the DNA and RNA in Various Rat Tissues. (29th April 2013) - Nie, Ben; Gan, Wei; Shi, Fei; Hu, Guo-Xin; Chen, Lian-Guo; Hayakawa, Hiroshi; Sekiguchi, Mutsuo; Cai, Jian-Ping
Abstract : The relationship between the oxidative damage of nucleic acids and aging of animals was investigated by analyzing the nucleic acids derived from various tissue specimens of naturally aged Sprague-Dawley (SD) rats. For this purpose, we established an accurate and sensitive isotope-diluted LC-MS/MS method to determine the levels of 8-oxo-7, 8-dihydro-2 ′ -deoxyguanosine (8-oxo-dGsn) in DNA and 8-oxo-7, 8-dihydroguanosine (8-oxo-Gsn) in RNA. An age-dependent increase in oxidative DNA and RNA damage was observed in the various organs examined, including the brain, liver, kidneys, and testes. Similar increases in the 8-oxo-dGsn and 8-oxo-Gsn contents were observed in three parts of the brain, the hippocampus, cerebral cortex, and cerebellum, among which, the values for the hippocampus were always the highest. When the oxidized guanosine metabolites were quantified with urine, a similar age-dependent increase was observed for both 8-oxo-dGsn and 8-oxo-Gsn. However, unlike the results of nucleic acid samples derived from the tissues, the amount of 8-oxo-Gsn was significantly higher compared to that of 8-oxo-dGsn, probably reflecting the fact that RNA degradation occurs more frequently than DNA degradation. Our finding indicates that the amount of urinary 8-oxo-Gsn could be considered as a biomarker for the sensitive measurement of oxidative stress and aging.